Eksplorasi Pengaruh Persepsi Aksesibilitas terhadap Pemilihan Moda Pekerja Komuter di Koridor LRT Jabodebek Lintas Bekasi - Zhafira, Muhammad Rivan; Andani, I Gusti Ayu (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
This study aims to explore the relationship between perceived accessibility and mode choice preferences of commuting workers, particularly in the newly operational Jabodebek LRT transportation corridor. The research compares the extent to which perceived accessibility explains actual accessibility and reduces perceived accessibility, measured through Likert-scale variables, using principal component analysis (PCA). Mode choice preferences are constructed using stated preferences, and factors such as socio-demographics, travel characteristics, and PCA results on perceived accessibility are estimated using multinomial logistic regression.The study’s findings indicate that, although the distance to LRT stations can be objectively measured, individual perceptions of this distance vary. Differentiation based on actual accessibility is also assessed to influence decision-making by travelers in choosing transportation modes. Several socio-demographic and travel factors are found to influence preferences for the LRT and bus modes. Meanwhile, subjective aspects, such as satisfaction with transportation modes, travel time, and travel costs, are found to significantly affect transportation mode preferences.